2019
DOI: 10.1155/2019/1801724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HTST Thermal Treatments on End-Use Quality Characteristics of Goat Milk

Abstract: Goat milk samples were pasteurized at high-temperature (72°C, 75°C, and 81°C) and in short-time (15 s and 25 s) combinations. Physical, chemical and microbial qualities of the pasteurized milk samples were evaluated 0, 2, 3, and 4 weeks of storage at 4°C. Despite the di erent thermal treatments, speci c-gravity and viscosity were comparatively stable immediately a er pasteurization (IAP). e viscosity of pasteurized milk at 81°C showed signi cant increase ( < 0.05) from 1.58 ± 0.18 to 2.30 ± 0.15 mPa s during f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Previous studies indicated that hermetic bag types provide alternatives to the use of chemicals in protecting seeds from insect damage and loss of germination (Kalsa et al, 2019; Mendesil et al, 2022; Prasantha et al, 2014). The present study stressed the performance of faba bean seeds stored in hermetic bags, and non‐hermetic bags over a 2‐year period of storage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that hermetic bag types provide alternatives to the use of chemicals in protecting seeds from insect damage and loss of germination (Kalsa et al, 2019; Mendesil et al, 2022; Prasantha et al, 2014). The present study stressed the performance of faba bean seeds stored in hermetic bags, and non‐hermetic bags over a 2‐year period of storage.…”
Section: Discussionmentioning
confidence: 99%
“…and 25 sec. ), whey protein denaturation is lower than in cow milk (Prasantha and Wimalasiri, 2019). In whey protein isolate solutions, whey protein denaturation increased by increasing the temperature from 72 °C to 85 °C, while the increased Ca concentration (1 to 5 mM CaCl 2 ) positively affects the whey protein aggregation (Joyce et al, 2018).…”
Section: Physicochemical Composition Of Wheymentioning
confidence: 95%
“…The boiled milk showed significant (P<0.05) increase in TA value 0.15±0.002. The increase in TA value of boiled sample could be due to the high heat treatment which was responsible for the degradation of lactose [52][53] .…”
Section: Titratable Aciditymentioning
confidence: 99%